Disaster management: identifying knowledge of community health nurses and its predictor factor - Ahayalimudin, Nurul'Ain; Ismail, Aniza (2014)
Background In recent year, disaster occurrences are increasing in numbers. Community health nurses (CHNs) as front lines are required to be prepared and act effectively during the events. With mounting numbers of health-related disasters, CHNs play very crucial roles to ensure the community receives appropriate services in which the outcomes will lead to the improvement of nursing care. In this study, the knowledge of community health nurses and predictor factor to the findings were investigated.